Quantum Nanorobotics: A Proposal for Quantum-Enhanced Actuation and Sensing at the Molecular Scale - Herri Trisna Frianto; Muhammad Firdaus A; Bilal Aslam (Journal of Tecnologia Quantica, 2025)
Quantum nanorobotics has emerged as a promising interdisciplinary field aimed at enabling precise manipulation and sensing at the molecular scale, where classical mechanical approaches face fundamental limitations. The purpose of this study is to propose a unified framework for quantum-enhanced actuation and sensing that leverages quantum mechanical effects as functional resources in nanorobotic systems. The research adopts a conceptual–theoretical design supported by computational modeling and simulation grounded in quantum mechanics and quantum control theory. Simulation-based analyses demonstrate that quantum-enhanced sensing achieves significantly higher sensitivity, lower noise variance, and reduced energy consumption compared to classical nanoscale sensors, while quantum-based actuation exhibits improved precision, faster response times, and enhanced stability under environmental noise. The integrated sensing–actuation architecture reveals synergistic performance gains that surpass isolated enhancements, enabling reliable molecular-scale navigation and task execution. The study concludes that quantum coherence and tunneling can be systematically engineered to overcome classical constraints in nanorobotics, establishing quantum-enhanced control as a viable design paradigm. The novelty of this research lies in its integrative conceptual framework that unifies quantum sensing and actuation within a single nanorobotic architecture, providing a foundational model for future experimental development and interdisciplinary applications.